Função pulmonar em indivíduos com SAOS antes e após o uso do CPAP: estudo randomizado duplo cego - Barros, Jefferson Luis de [UNESP] (2014)
Introduction: Obstructive Sleep Apnea Syndrome (OSAS) is characterized by the complete or partial intermittent obstruction of the upper airway due to colapse of the pharyngeal muscles, causing the cessation or reduction of the respiratory airflow and, consequently, intermittent hypoxia and hipercapnia. The most common daytime symptom is excessive daytime sleepiness, reported already as long as 2000 years ago. Obesity is the most frequent reversibel causal fator, being physical activity an important component for its treatment. We hypothezised that OSA patients would show disordered sleep quality, higher daytime sleepiness and lower disposal for physical activity, beside changes at the spyrometric fraction FEF25%-75%, as being the componente related to unvoluntary expiration phase without interference of the expiration muscles. The adequate use o of nighttime CPAP would improve these conditions, even after a short period of intervention. Aims: To study the parameters for sleep quality, excessive daytime sleepiness, diposal for physical activity and of spirometry in OSA patients, before and after CPAP therapy. Methods: This double-blind, randomized study was approved by the local Ethics Comission. There were invited patients at follow-up at the ambulatory for non-invasive ventilation, aged 30 to 75 years old, both genders, all diagnosed OSAS by full-night polysomnography. They were randomized for two groups without the knowledge ot the physical therapeut, Group I receiving the CPAP with minimal pressure at 4 cmH2O and Group II at ideal therapeutic pressure. An equipment with blinded visor was disposed to all patients, thus, nor the patients, neither the physical therapeut had access to the ventilatory data. At two moments, before and after 7 days of CPAP treatment, all patients answered the questionnaires for daytime sleepiniess (Epworth Sleepiniess Scale), sleep quality (Pittsburgh questionnaire) and disposal for physical activity ...